Underclass, Culture of Poverty and the Research in Sociomoral Competence among the Poor - Kowalewska, Karolina (ETHICS IN PROGRESS, 2018)
In this paper, I consider whether a theoretically defined concept of underclass can be helpful in social scientific discourse. I analyze, review and categorize the concept of a underclass and I made some suggestions for a use of the concept application in the study of social, psychological and moral consequences of poverty. It begins with a discussion of the continuing and pervasive appeal of structural explanations as the root cause of poverty. Then are also examined cultural theories, which by contrast find explanation for poverty in various elements of culture (ex. cultural traits of poor are thought to be different from those of the rest society). A third, a synthetic review of the urban underclass concept is explored. The article also describes the concept of a „culture of poverty” (taking into account the context of the subculture) and „lower class value stretch” as influential concepts in analyses of contemporary poverty and in explanations of the behavior of the poor.